The Right of Women with Disabilities to Work in the EU: A Study of the Current Reality and the New Mechanisms - Litim, Nadia (Journal of Legal Studies and Researches, 2023)
This study aims to highlight the reality of women with disabilities in the EU and to analyze the various legal and institutional mechanisms in order to guarantee the right to work for women with disabilities. The study reached a number of conclusions, the most important of which is that the EU countries witness a great variation in the rates of employment of women with disabilities; therefore, it adopted many new measures.